A New Species of Dipolydora (Annelida, Spionidae) from deep-water methane seep habitats off Louisiana (Gulf of Mexico), a borer in shells of the gastropod Kanoia meroglypta - Blake, James A. (Zootaxa, 2025)
A new shell-boring spionid polychaete of the genus Dipolydora is described from the gastropod, Kanoia meroglypta (Family Trochidae), collected from mussel beds on the continental slope off Louisiana at a depth of 617 m in an area of methane seepage. The new species belongs to a large group of Spionidae comprising the Polydora complex (ca. 178 species) having a modified setiger 5. The new species, Dipolydora walkerae sp. nov., belongs to a small group of Dipolydora having large hooked spines on setiger 5 surmounted with a crest or cloak of fine bristles or fibrils and has posterior notopodia with modified acicular spines. The majority of polydorins are from intertidal or continental shelf depths; deep-water accounts are few and poorly documented. The new species is compared with its closest congener, Dipolydora armata. Previous accounts of shell-boring polydorins from offshore are tabulated by the depth of occurrence and discussed. The new species represents the deepest confirmed record for a shell-boring spionid polychaete.